Best Answer

-6x3 + 4x7 - 0.8x2 + x4 - 5x5 =

4x7 - 5x5 + x4 - 6x3 - 0.8x2 =

x2 (4x5 - 5x3 + x2 - 6x - 0.8)

Q: -6x3 plus 4x7-0.8x2 plus x4-5x5

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

The answer is 37.

6X3 is 6, 3 times. 6, 3 times is 6+6+6. 6+6+6=18. 6X3=18. :)

14

6x3=18

(12x3 + 14x2 + 14x + 2)/(4x + 2) simplify= (6x3 + 7x2 + 7x + 1)/(2x + 1)1. 6x3 + 7x2 - 3x2(2x + 1) = 6x3 - 6x3 + 7x2 - 3x2 = 4x2; bring down 7x2. 4x2 + 7x - 2x(2x + 1) = 4x2 - 4x2 + 7x - 2x = 5x bring down 13. 5x + 1 - 2(2x + 1) = 5x - 4x + 1 - 2 = x - 1 the reminderThus, (6x3 + 7x2 + 7x + 1)/(2x + 1) = 3x2 + 2x + 2 + (x - 1)/(2x + 1)and(12x3 + 14x2 + 14x + 2)/(4x + 2) = 3x2 + 2x + 2 + (2x - 2)/(4x + 2).

Related questions

The answer is 37.

6x3 - 27x2 + 3x + 36 = 3 (x - 4) (x + 1) (2x - 3)

6x3 - x2 + 17 = 2x2 + 47 6x3 - x2 - 2x2 = 47 - 17 x2(6x - 1 - 2) = 30 this is the simplest factorisation.

10x + 8x - 6x3 + 4x2 + 12x3 - x add the like terms. all the x's are like terms. al the x squared are like terms. all the x cubed are liked terms. 6x3 + 12x2 + 9x

2x3

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

(16 + 3) + (16 x 3) = 19 + 48 = 67

(3x - 1)(2x2 - 2x - 1)

zero

24x^5 + 24x^3 = 24x^3(x^2 + 1)

6x³ +12x + 18 = 6(x + 1)(x² - x + 3)

6x(3-3)x(2+12)